2001
DOI: 10.1111/j.1349-7006.2001.tb01103.x
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Vascular Endothelial Growth Factor and Nm23 for the Diagnosis of Occult Metastasis in Non‐small Cell Lung Cancer

Abstract: We assessed the association of vascular endothelial growth factor (VEGF) and nm23 expression with occult micrometastasis in lung cancer. As destination sites for micrometastasis, we scrutinized lymph node (LN) and bone marrow (BM) specimens. For LN, 122 stage I patients who had received curative operations were studied. As regards BM, 203 patients in stage I-IV who underwent operations were registered. Immunohistochemical anti-cytokeratin staining was used to detect microdissemination of cancer cells. The VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…MVD in breast cancer tissues is closely related to distant metastasis and survival time, having been conWrmed in similar researches on stomach cancer, melanoma, non-small cell lung cancer and prostate cancer (Zhu et al 2005;Imamura et al 2007;Bono et al 2002). Ohta et al (2001) assessed the association of VEGF with occult micrometastasis in 285 cases with lung cancer. The results showed that the increased expression of VEGF within primary tumors was signiWcantly associated with LN and BM microdissemination, indicating possible value of using biological markers to predict micrometastasis in lung cancer.…”
Section: Discussionmentioning
confidence: 92%
“…MVD in breast cancer tissues is closely related to distant metastasis and survival time, having been conWrmed in similar researches on stomach cancer, melanoma, non-small cell lung cancer and prostate cancer (Zhu et al 2005;Imamura et al 2007;Bono et al 2002). Ohta et al (2001) assessed the association of VEGF with occult micrometastasis in 285 cases with lung cancer. The results showed that the increased expression of VEGF within primary tumors was signiWcantly associated with LN and BM microdissemination, indicating possible value of using biological markers to predict micrometastasis in lung cancer.…”
Section: Discussionmentioning
confidence: 92%
“…Streptavidin-biotin-peroxidase, scale bar=100 μm NM23-H1 and NM23-H2 are abundant and most studied [1,6,20,26]. Historically, several antibodies raised against NM23 were analyzed with respect to a wide range of neoplasms [5,12,16,22,23,27]. Many studies were completed before the characterization of all members of the NM23 family and consequently it is not clear which family member was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis appears to be a significant prognostic factor in patients with resected NSCLC in most studies [233,[245][246][247][248][249]. However, not all studies showed that angiogenesis is associated with an adverse prognosis [45,250].…”
Section: Alteration Of Vascular Endothelial Growth Factor Receptor Inmentioning
confidence: 99%